Electronic Agenda (E-Agenda) Systems for Keeping School Archives in Indonesia: Is There A Case in Managing of Archive through Manual Agenda System? - Oktarina, Nina; Widodo, Joko; Murwatiningsih, Murwatiningsih; Murniawaty, Indri; Sholikah, Mar’atus (KnE Social Sciences, 2019)
The objective of the study was to develop e-agenda system to support archive management at school. During this time archival management in schools still uses manual systems in recording archives. The use of manual recording systems is not effective because the archive search process cannot be done quickly and accurately. Therefore,e-agendasystemwasdevelopedtoovercometheseproblems.Thesystem was developed based on Ms. Access program. It was a Research and Development (R&D) study. The data were collected by observation, interview, documentation, and questionnaire. Then; the data were analysed quantitatively; it was t-test on the paired data to test the difference of the actual and the new model. It was also analysed qualitatively through the data triangulation. The results showed that e-agenda system can support better archive management. Therefore; it is suggested for administrative ofﬁcer at school to implement e-agenda system to support archive management because e-agenda system easy to implement and does not require expensive fees to design it. Keywords: E-Agenda, Archive, Management